Are There Any Common Genetic Risk Markers for Rheumatoid Arthritis and Periodontal Diseases? A Case-Control Study - Susanne Schulz; Natalie Pütz; Elisa Jurianz; Hans-Günter Schaller; Stefan Reichert (Mediators of Inflammation)
Background. Several studies suggest that there is a biologically plausible connection between rheumatoid arthritis (RA) and periodontal diseases (PD). Both disorders are characterized as multifactorial diseases potentially sharing common risk factors. Based on the inflammatory nature of RA and PD, the impact of genetic variations of genes of the immune system on both diseases was studied in this study. Materials and Methods. We conducted a case-control study (n=201) comparing 101 RA patients suffering from periodontal disease of different severities (no/mild PD vs. severe PD) with 100 systemically healthy controls without RA and severe PD. The genotype, allele, and haplotype distributions of 22 SNPs of 13 pro- and anti-inflammatory cytokines were assessed applying sequence-specific PCR. Results. Evaluating the impact of cytokine SNPs in RA, we identified the G allele of rs1801275 in IL4Rα (p=0.043) and the G allele of rs361525 in TNFα (p=0.005) as disease-associated risk factors in bivariate analyses. In multivariate analyses, these significant associations could not be proven. The A allele of rs2430561 in IFNγ was indicative for severe periodontitis among the patients with rheumatoid arthritis (p=0.039). Investigating the impact of rs2430561 in IFNγ on comorbidity using binary logistic regression analyses, the A allele was confirmed as an independent risk factor for severe periodontal disease and RA (p=0.024). Conclusions. These results emphasize the association of genetic variations in proinflammatory cytokines (TNFα and IFNγ) and cytokine receptor (IL4Rα) and RA and periodontal diseases. In multivariate analyses, the A allele of IFNγ was proven to be a significant marker of RA and PD comorbidities. The study broadens the knowledge about disease-specific differences in genetic composition and provides an improved understanding of a possible association of both diseases.